Lippia javanica (Zumbani) herbal tea infusion attenuates allergic airway inflammation via inhibition of Th2 cell activation and suppression of oxidative stress - Mvuyisi O. M. Mfengu; Mathulo Shauli; Godwill A. Engwa; Hannibal T. Musarurwa; Constance R. Sewani-Rusike (BMC, 2021)
Abstract Background Lippia javanica (lemon bush) is commonly used in the treatment of respiratory ailments, including asthma in southern African countries but there is no scientific evidence to support this claim. This study investigated the anti-inflammatory, antioxidant and anti-asthmatic effects of L. javanica using a rat model of asthma. Methods A 5% w/v L. javanica tea infusion was prepared and characterised by liquid chromatography-mass spectrometer (LC-MS). Animals were intraperitoneally sensitized with ovalbumin (OVA) and subsequently challenged intranasal with OVA on day 15 except the control group. Animals were grouped (n = 5/group) for treatment: unsensitised control, sensitised control, sensitised + prednisolone and sensitised + L. javanica at 50 mg/kg/day and 100 mg/kg/day - equivalent to 1 and 2 cups of tea per day, respectively. After 2 weeks of treatment, bronchoalveolar lavage fluid (BALF) was collected for total and differential white blood cell (WBC) count. Nitric oxide (NO), lipid peroxidation and antioxidants were also assessed in BALF. Ovalbumin specific IgE antibody and inflammatory cytokines: IL-4, IL-5, IL-13 and TNF-alpha were measured in serum. Lung and muscle tissues were histological examined. Results L. javanica was rich in phenolic compounds. OVA sensitisation resulted in development of allergic asthma in rats. L. javanica treatment resulted in a reduction in total WBC count as well as eosinophils, lymphocytes and neutrophils in BALF. L. javanica inhibited Th2-mediated immune response, which was evident by a decrease in serum IgE and inflammatory cytokines: IL-4, IL-5, IL-13 and TNF-α. L. javanica treatment also reduced malondialdehyde (MDA) and NO, and increased superoxide dismutase, glutathione and total antioxidant capacity. Histology showed significant attenuation of lung infiltration of inflammatory cells, alveolar thickening, and bronchiole smooth muscle thickening. Conclusion L. javanica suppressed allergic airway inflammation by reducing Th2-mediated immune response and oxidative stress in OVA-sensitized rats which may be attributed to the presence of phenolic compound in the plant. This finding validates the traditional use of L. javanica in the treatment of respiratory disorders.